Functional food knowledge and use in individuals with type 2 diabetes and the relevant factors - Otay Lule, Nezihe; Simsek, Hatice; Ylmaz, Simge; Cavdar, Umit (Progress in Nutrition, 2019)
This study aimed to determine the knowledge and use of functional foods in individuals with type 2 diabetes who came to Dokuz Eylul University Hospital’s Endocrinology Polyclinic, were aged 18 years or older, and diagnosed with type 2 diabetes no earlier than six months from before the study began. The study also focused on the associated factors. This is a cross-sectional study. In an infinite population, the smallest sample size to be achieved was 196 with 50% frequency and 7% error margin.